THE EFFECT OF STORE IMAGE, SERVICE QUALITY AND PRIVATE LABEL BRAND IMAGE TOWARD PURCHASE INTENTION ON VALUE PLUS HYPERMART MALANG TOWN SQUARE MALANG - Sunu, Made Shri Wijaya; Hendrawan, Dimas (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to determine the effect Store Image, Service Quality, and Private Label Brand Image on Purchase Intention of Hypermart Private Label Brand Malang Town Square Malang in  partially.  The  research  is  explanatory research  when  explains  the causal relation between the variables through hypothesis testing. The data collection technique of this study is uses questionnaires and literature study. This  study  used  190  samples  of Hypermart‟s  consumers in Malang  Town  Square, Malang. Those samples were taken using a purposive sampling technique. Test equipments that are used for testing the research instrument are validity test, reliability test, and classical assumption test. The analytical methods that were used are multiple linear regression and hypothesis testing are conducted with t test using SPSS 16. The result of this study shows that in partial with using testing t is concluded that Store Image and Private Label Brand Image have significant effect towards Purchase Intention, while Service Quality has no  effect in partially. New fact that found in this study indicates that respondents agree that Service Quality in Hypermart Malang Town Square is neutral, however they are not make/influence them in the purchase intention of private label brand in Hypermart.   Key Words: Store Image, Service Quality, Private Label Brand Image, Purchase Intention